1996
DOI: 10.1097/00005053-199606000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Post-Vietnam Stress Syndrome Revisited

Abstract: Malignant Post-Vietnam Stress Syndrome describes a severe form of combat-related posttraumatic stress disorder. We update the concept of Malignant Post-Vietnam Stress Syndrome, considering the effects of repeated severe traumatization, exposure to atrocities, and a variety of comorbid conditions. An illustrative case report demonstrates an interdisciplinary treatment approach, combining case management, brief hospitalizations, symptom-directed use of medications, and supportive psychotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The results of this study suggest that even within the population of help-seeking Vietnam combat veterans with PTSD, differences in symptom severity and adjustment are evident. These results provide partial support for the theoretical conceptualization of MPVSS, as outlined by Rosenheck (1984Rosenheck ( , 1985 and Lambert and his colleagues (Lambert et al, 1996). In particular, across subsamples, individuals in Cluster 2 differed from the other veterans with chronic PTSD in that they reported higher current levels of interpersonal violence and physical health problems.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The results of this study suggest that even within the population of help-seeking Vietnam combat veterans with PTSD, differences in symptom severity and adjustment are evident. These results provide partial support for the theoretical conceptualization of MPVSS, as outlined by Rosenheck (1984Rosenheck ( , 1985 and Lambert and his colleagues (Lambert et al, 1996). In particular, across subsamples, individuals in Cluster 2 differed from the other veterans with chronic PTSD in that they reported higher current levels of interpersonal violence and physical health problems.…”
Section: Discussionsupporting
confidence: 56%
“…
This study investigated whether a subgroup of veterans with malignant posttraumatic stress syndrome, as described by Rosenheck (1985) and Lambert et al (1996), could be identified via cluster analysis within two samples of Vietnam veterans with combat-related posttraumatic stress disorder (PTSD). In the initial subsample (n ϭ 157), four clusters were identified, including a subgroup that scored consistently higher on measures This study was supported by NCI P01-CA-81595.
…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…PTSD is a disorder that is notoriously difficult to treat 4,5,8 especially in the veteran population, 6,9 and treatment response in those with chronic PTSD is highly variable. In the last 10 years, several drug classes (ie, benzodiazepines, antidepressants, anticonvulsants, and antipsychotic agents) have been studied in the treatment of PTSD.…”
mentioning
confidence: 99%